(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The subject of food security has received much attention in the recent past because food security is a significant worldwide issue . Despite decades of effort to end malnutration and hunger in different parts of the world, a satisfactory level of success has not been achieved. It is argued that the various approaches of food security should also address social, economic and political aspects, in addition to their technical and environmental dimensions. In the recent past the concept of governance has been increasingly applied to the notion of food security. Some important elements of food security are availability of food, access to food, utilization of food and the stability of food. In the present study an attempt is made to perform a systematic review of both academic and grey literature of food security which explain the food security governance system and thereby suggest a few recommendations for the future. The study was basically desk based.